Facebook as a tool for learning purposes: Analysis of the determinants leading to improved students' learning. (July 2015) - Nkhoma, Mathews; Cong, Hiep Pham; Au, Bill; Lam, Tri; Richardson, Joan; Smith, Ross; El-Den, Jamal
The study described in this article aims to investigate the use of out-of-class communication between students and instructors using Facebook as a means of interaction for learning. How often/how much students use such an online social network and the clarification as to the reasons for online communication are the two exogenous variables used to measure the perceptions that students have about the impact of online social networking on their learning. How students perceive the quality of the content of student–instructor interaction on Facebook is treated as a mediating variable in the research model. How students perceive their performance is used as a proxy for their learning outcomes and is treated as the endogenous variable. A questionnaire was developed and used, and the analysis of the data gathered from the questionnaire was conducted using a measurement model and a structural model. The results of the study revealed that how often/how much students use an online social network and the reasons that they give for using online communication have a significant positive impact on how they perceive the quality of the content of student–instructor interaction on Facebook. In addition, the results demonstrated that the use of Facebook has a negative impact when it comes to the students' perceptions of the quality of the content of student–instructor interaction on their perceived performance.